1995
DOI: 10.1007/bf00048814
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance in dogs to repeated infestation with Ixodes scapularis (Acari: Ixodidae) reduces tick viability and reproductive success

Abstract: The purpose of this study was to determine whether dogs develop acquired resistance to adult Ixodes scapularis infestation in an experimental model. Five dogs were each infested with ten mating pairs of ticks every week for 7 consecutive weeks, another five dogs were each infested with ten mating pairs once every 2 weeks for 10 weeks and four dogs served as controls not exposed to ticks. All ticks were allowed to feed to repletion and were collected only after dropping from the host. Several variables were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…131 The immune responses recruited to the tick bite site on tick-resistant animals are thought to be detrimental to tick feeding resulting in early tick detachment and decreased engorgement weights. Similar observations with additional tick species, as well as the generation of ATR in rabbits, mice and cattle [132][133][134][135] have demonstrated that the phenomenon of ATR is widespread in tick-host interactions.…”
Section: Animal Model S Of Acqu Ired Tick Re S Is Tan Cesupporting
confidence: 73%
“…131 The immune responses recruited to the tick bite site on tick-resistant animals are thought to be detrimental to tick feeding resulting in early tick detachment and decreased engorgement weights. Similar observations with additional tick species, as well as the generation of ATR in rabbits, mice and cattle [132][133][134][135] have demonstrated that the phenomenon of ATR is widespread in tick-host interactions.…”
Section: Animal Model S Of Acqu Ired Tick Re S Is Tan Cesupporting
confidence: 73%
“…Canines experimentally infested with adult I. scapularis developed acquired resistance, which reduced tick viability and oviposition with each successive exposure (11). Acquired resistance to the vector might reduce transmission of spirochetes.…”
mentioning
confidence: 99%
“…Some differences between the results obtained by the above-mentioned authors and the results of the present study (the percentage of normally hatched larvae) stem from the different degree of host immunisation (different re-infestation time) and from different methodologies employed (different experimental conditions). In I. scapularis feeding on immunised dogs, oviposition disturbances and decreased larval survival in the first generation were observed [46]. The current results suggest that co-feeding 2 different tick species on the same host may partially counteract the adverse influence of host immunity in repeated invasions.…”
Section: Discussionmentioning
confidence: 55%